Alzheimer disease and the prion disorders amyloid beta-protein and prion protein amyloidoses. - Price, D L (1993)
Alzheimer disease and the prion disorders/spongiform encephalopathies share many common features. These chronic, progressive, sometimes familial diseases of the central nervous system are characterized by the presence of different types of amyloid deposits in the brain. This review provides a perspective on these two types of neurodegenerative disorders.